Gene editing: a guided tour of a biosafety level 2 lab - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
This video welcomes you to the world of gene editing with an exclusive tour of a Biosafety Level 2 lab. We break down the intricate process of gene editing, from the science behind it to the practical steps taken in a controlled lab environment. The video also provides a fascinating glimpse into the future of biotechnology and discover how cutting-edge research is transforming agriculture.